Analisis Persepsi Masyarakat tentang Air Bersih dan Kualitas Air di Desa Ibul Besar III - Rosyada, Amrina; Ardillah, Yustini; Oktivaningrum, Rafika; Pratiwi, Laura Dwi (LPPM Hang Tuah Pekanbaru, 2024)
Various human activities in the surrounding area cause surface and groundwater pollution. The people of Ibul Besar III village face difficulties in accessing proper sanitation facilities as they still use river water as their main source of clean water. The quality of the local river water appears to be murky and does not meet the BML, thus posing the risk of causing disease problems such as diarrhea, skin infections, etc. This research aims to analyze the quality of clean water and the community's perception of clean water in Ibul Besar III village. The research design uses a qualitative approach through in-depth interview methods. The informants are identified through purposive sampling, namely up to 8 people. The results show that people's perception is that they use river water as their main source of clean water because there are no other sources that can be used. The local people say that the river water is only suitable for bathing and washing. Some communities try to treat the water before using it by adding chlorine and sedimentation. Based on the results of water quality tests, temperature parameters, odour, TDS, e.coli and total coliform meet BML standards, while pH, color, and turbidity do not meet BML standards. It is necessary to provide facilities and infrastructure to support the availability and treatment efforts such as simple water filtration media from the village government to obtain clean water that meets the specified BML standards.